Modeling-Based Investigation of the Effect of Noise in Cellular Systems - Gonze, Didier; Gérard, Claude; Wacquier, Benjamin; Woller, Aurore; Tosenberger, Alen; Goldbeter, Albert; Dupont, Geneviève (Frontiers in Molecular Biosciences, 2018)
Noise is pervasive in cellular biology and inevitably affects the dynamics of cellular processes. Biological systems have developed regulatory mechanisms to ensure robustness with respect to noise or to take advantage of stochasticity. We review here, through a couple of selected examples, some insights on possible robustness factors and constructive roles of noise provided by computational modeling. In particular, we focus on (1) factors that likely contribute to the robustness of oscillatory processes such as the circadian clocks and the cell cycle, (2) how reliable coding/decoding of calcium-mediated signaling could be achieved in presence of noise and, in some cases, enhanced through stochastic resonance, and (3) how embryonic cell differentiation processes can exploit stochasticity to create heterogeneity in a population of identical cells.